2017
DOI: 10.1016/j.ejvs.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

EVAR with Flared Iliac Limbs has a High Risk of Late Type 1b Endoleak

Abstract: Patients treated with iliac limbs ≥20 mm had a fivefold higher risk of late (mean 37 months) type 1b endoleak compared with patients treated with a distal iliac limb diameter <20 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 33 publications
1
25
1
1
Order By: Relevance
“…McDonnell et al 10 describe the higher rate of type Ib endoleak 7% after a mean follow-up of 30 months when flared iliac limb was used. Gray et al 14 recently published similar results of a 7.5% incidence with type Ib endoleak. These results also indicated that the limb graft with a diameter of !…”
Section: Discussionmentioning
confidence: 65%
“…McDonnell et al 10 describe the higher rate of type Ib endoleak 7% after a mean follow-up of 30 months when flared iliac limb was used. Gray et al 14 recently published similar results of a 7.5% incidence with type Ib endoleak. These results also indicated that the limb graft with a diameter of !…”
Section: Discussionmentioning
confidence: 65%
“…In the long period the BBT results demonstrate worst trend: Gray et al (2017) presented 61 patients with a CIA diameter of > 20 mm with high type 1b rate endoleak (18%) compared with standard limbs (4%) with mean follow up of 53 months. Other reports (EURO-STAR database) (Griffin et al 2015;Hobo et al 2007) showed a high rate (9-14%) of late iliac complications in patients with BBT including type 1b endoleak and other iliac complications.…”
Section: Discussionmentioning
confidence: 98%
“…The bell-bottom technique (BBT) has been used for many years in patients with abdominal aortic aneurysm (AAA) and concomitant wide or aneurysmal CIA with distal landing zone diameter from 18 up to 25 mm and length more than 20 mm (Torsello et al 2010;Gray et al 2017). This anatomical feature can be suitable also for iliac branch device (IBD) that in the last years has become the most popular treatment (Donas et al 2017;Simonte et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, all of these solutions are associated with significant operation time and contrast amount [8] . In addition, the FL technique could be linked with a high rate of dilatation with Type Ib endoleak, five times more than the corresponding less than 20 mm CIA diameter [9] . Additionally, the difficulty in later usage of IBD necessitates the usage of trans-axillary access with increased risk of stroke [9,10] .…”
Section: Discussionmentioning
confidence: 99%